The book and the World Wide Web - Vaupotič, Aleš (Primerjalna književnost, 2012)
The essay considers the effects of internet-based communication on the book as a carrier of a message. An examination of Teo Spiller's "sonnet-like" web projects and of web archives such as the Stanford Encyclopedia of Philosophy shows which aspects of the book have changed or were improved in web-based communication forms, and which aspects are book-specific and thus retain their value in the Internet era.
Keywords: Google books; medmrežje; spletna komunikacija; referenčna literatura; računalniško branje; sistem za upravljanje z vsebinami; novomedijska literatura; kibertekst